Translational Research Platform for Malignant Central Nervous System Tumors - Kensuke TATEISHI (Neurologia Medico-Chirurgica, 2024)
Some central nervous system (CNS) malignancies are highly aggressive and urgently need innovative treatment strategies to improve prognosis. A significant concern for therapeutic development is the time-consuming nature of developing treatments for CNS tumors. Therefore, a rapid and efficient translational approach is needed to address this problem. Translational and reverse translational research aims to bridge the gap between laboratory data and clinical applications and has been developed in the field of neuro-oncology. This study presents our translational platform systems for malignant CNS tumors, which combine an intraoperative integrated diagnostic system and comprehensive in vitro and in vivo assay systems. These laboratory systems may contribute to a better understanding of tumor biology and the development of novel therapeutic strategies for the poor prognosis of CNS tumors.